An integrated metabolomics approach for the research of new cerebrospinal fluid biomarkers of multiple sclerosis1. Issue 6 (19th June 2015) - Pieragostino, Damiana; D'Alessandro, Michele; di Ioia, Maria; Rossi, Claudia; Zucchelli, Mirco; Urbani, Andrea; Di Ilio, Carmine; Lugaresi, Alessandra; Sacchetta, Paolo; Del Boccio, Piero
<x xml:space="preserve">Abstract</x> (1) Lipid profiling in MuS and OND patients. (2) Search of alterations associated with MuS. (3) Characterization of differences.